2017
DOI: 10.1111/jphp.12784
|View full text |Cite
|
Sign up to set email alerts
|

Essential oils and hydrophilic extracts from the leaves and flowers of Succisa pratensis Moench. and their biological activity

Abstract: The results suggest great antibacterial activity of the oils and high antioxidant activity of the methanol extract and may justify the application in treating infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Comparison of the effect of isolated luteolin and apigenin 7-glucosides with herb extracts indicated a stronger inhibitory potential of S. pratensis leaves' extract. A high content of flavonoids in this preparation (1.18%) in comparison with the flowers extract (0.23%) may be responsible for this effect (Witkowska-Banaszczak & Długaszewska, 2017).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Comparison of the effect of isolated luteolin and apigenin 7-glucosides with herb extracts indicated a stronger inhibitory potential of S. pratensis leaves' extract. A high content of flavonoids in this preparation (1.18%) in comparison with the flowers extract (0.23%) may be responsible for this effect (Witkowska-Banaszczak & Długaszewska, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…In our earlier report we showed that in Succisa pratensis herb's methanolic extract, there is a substantial amount of flavonoids, including luteolin and apigenin 7-glucosides (Witkowska-Banaszczak & Długaszewska, 2017).…”
Section: Introductionmentioning
confidence: 89%
“…It has been used for treatment due to its antioxidant, antiinflammatory, local anaesthetic, antinociceptive, antiseptic, antibacterial, and antifungal effects as well as for their beneficial effects on the cardiovascular system [143]. The studies of T. vulgaris and Succisa pratensi revealed that thymol is able to block ergosterol synthesis and ultimately caused pore formation in the membrane [49,99]. Tannins (Fig.…”
Section: Active Compoundsmentioning
confidence: 99%
“…Volatile siloxanes like cyclotetrasiloxane are present in volatile oils of most of herbs (zhenhs etal). Hexadecanoic acid (palmitic acid) one of an important fatty acid ester has been identified in the distillate has reported antioxidant property [13]. 9, 12-octadecadienoic acid (z, z) (linoleic acid) is a poly unsaturated essential fatty acid (omega-6 fatty acid) that is very important for human nutrition and cardiovascular health.…”
Section: Ktd: Tic +mentioning
confidence: 99%
“…Gas chromatograph of kadukkai theeneer Pharmacological significance of compounds spotted in kadukkai theeneer[13][14][15][16][17][18] …”
mentioning
confidence: 99%